The conqueror motif in chapters 12-13: a heavenly and an earthly perspective in the Book of Revelation - Shin, E. C. (Verbum et ecclesia, 2007)
The theme of the conqueror motif in the book of Revelation is one of the prominent themes. The theme of the conqueror motif provides various symbolical messages from an exegetical and theological perspective. An alternative symbolic perspective provides a heavenly perspective and the symbolic transformation. Various images such as salvation for the conquerors and judgment of the evil ones, or victory of the Lamb and defeat of Satan, transform our earthly perspective into the heavenly perspective, and give us a new understanding as to how the conquerors should see the world. To provide the conquerors with a new understanding is to give them a reversed effect as a marginalized group and to reveal deep spiritual conflict between God and Satan. Who is in control in history? With the result of the heavenly war between Michael and the dragon in 12:7-9, John proclaims the victory of God, who is the real conqueror, and provides the heavenly perspective that God is in control of the cosmos, as well as of history.